Routledge Handbook of Crime Science - Wortley, Richard; Sidebottom, Aiden; Tilley, Nick; Laycock, Gloria (Routledge International Handbooks, 2019)
Crime science is precisely what it says it is: the application of science to the phenomenon of crime. This handbook, intended as a crime science manifesto, showcases the scope of the crime science field and provides the reader with an understanding of the assumptions, aspirations and methods of crime science, as well as the variety of topics that fall within its purview. Crime science provides a distinctive approach to understanding and dealing with crime: one that is outcome-oriented, evidence-based and that crosses boundaries between disciplines. The central mission of crime science is to find new ways to cut crime and increase security. Beginning by setting out the case for crime science, the editors examine the roots of crime science in environmental criminology and describe its key features. The book is then divided into two sections. The first section comprises chapters by disciplinary specialists about the contributions their sciences can make or have already made to crime science. The second section of the book comprises a series of exemplary case studies in crime science, showing a wide range of the kind of work that crime scientists do. The editors conclude by drawing on the preceding contributions, as well as germane areas of research, to offer a thoughtful consideration of future directions for crime science. This book is essential reading for social scientists and scientists alike and marks a new phase in the study of crime and its detection and prevention.